Adequacy of single phase natural circulation loop in parabolic trough collector. (2022) - Nakul, S.; Arunachala, U.C.
Abstract: A larger diameter single phase natural circulation loop is analysed, with a focus on parabolic trough application. Since the geometry chosen is highly unstable, loop tilt is invoked, which resulted in steady state. Although, inclination of 2° initiated the stability process, for better response 4°–6° is suggested. To generate good number of data, 1-D model is validated and extended to different tilts and solar irradiance. Although loop fluid flow rate enhances with irradiance level, higher tilt negates the performance level notably. The gist of the present experimental cum theoretical study is, the application of a natural circulation loop in parabolic trough is conceivable with desired modifications in the present system.